Positive selection analysis of Cyt proteins from Bacillus thuringiensis: a conservative trend driven by negative (purifying) selection - Palma, Leopoldo; Sauka, Diego Herman; Berry, Colin; Peralta, Cecilia (Elsevier, 2024)
Bacillus thuringiensis is a Gram-positive entomopathogenic bacterium that produces different pesticidal proteins: vegetative insecticidal proteins (Vpb1/Vpa2, Vip3, and Vpb4) during vegetative growth, which are secreted to the culture medium, and δ–endotoxins (Cry and Cyt) during sporulation, which accumulate into parasporal crystals. Cyt proteins are the smaller subset of δ–endotoxins targeting Diptera species. While Cry and Vip3 proteins undergo positive selection, our analysis suggests that Cyt proteins evolve following a conservative trend driven negative (purifying) selection.